2020
DOI: 10.3389/fphys.2020.572040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Flow Restriction on Leukocyte Profile and Muscle Damage

Abstract: Muscle damage affects the blood leukocyte profile. Resistance exercise (RE) with blood flow restriction (BFR) attenuates exercise-induced muscle damage (EIMD). Purpose To evaluate muscle damage and the leukocyte profile in response to RE+BFR and to compare with high intensity RE. Methods Twenty volunteers performed the RE in the leg press apparatus in the following groups: RE80, 80% of 1RM (3 × until concentric muscle failure); RE40+BFR, 40% of 1RM with BFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Moreover, muscle hypertrophy and strength gain induced by low‐load BFR‐RE is comparable to those induced by high‐load NBFR‐RE (Centner et al, 2019 ; Lixandrão et al, 2018 ). Furthermore, low‐load BFR‐RE can be performed more frequently than high‐load RE owing to lower muscle damage following RE (Dos Santos et al, 2020 ; Takarada et al, 2000 ); thus, BFR‐RE‐induced muscle adaptation can be obtained early within a short‐term (e.g., 2 weeks) because of increased training frequency throughout this period (Abe et al, 2005 ). Therefore, low‐load BFR‐RE is now recognized as a beneficial strategy to replace high‐load RE.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, muscle hypertrophy and strength gain induced by low‐load BFR‐RE is comparable to those induced by high‐load NBFR‐RE (Centner et al, 2019 ; Lixandrão et al, 2018 ). Furthermore, low‐load BFR‐RE can be performed more frequently than high‐load RE owing to lower muscle damage following RE (Dos Santos et al, 2020 ; Takarada et al, 2000 ); thus, BFR‐RE‐induced muscle adaptation can be obtained early within a short‐term (e.g., 2 weeks) because of increased training frequency throughout this period (Abe et al, 2005 ). Therefore, low‐load BFR‐RE is now recognized as a beneficial strategy to replace high‐load RE.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have shown that BFR in combination with low‐load exercise does not cause muscle damage (Dos Santos et al, 2020; Loenneke et al, 2014; Neto et al, 2018; Nielsen et al, 2017), conflicting results related to the effects of LL‐BFR on muscle damage were also reported (Alvarez et al, 2020; Sieljacks et al, 2016). One study indicated that LL‐BFR can induce significant muscle damage, causing variations in the indirect marker levels of muscle damage, such as increased inflammation, prolonged swelling, increased muscle soreness, and increased serum protein concentrations, decreased muscle strength and decreased ROM (Sieljacks et al, 2016).…”
Section: Introductionmentioning
confidence: 99%